2019
DOI: 10.22495/cgsrv3i1p4
|View full text |Cite
|
Sign up to set email alerts
|

Corporate voluntary disclosures and board independence of Indian companies

Abstract: Annual reports apart from being a means of communication are used as a vehicle of building and improving corporate image. Even the government and its institutions presiding over the corporate sector emphasize on additional disclosures related to corporate governance, corporate social responsibility, corporate sustainability etc. apart from more voluntary financial disclosures to enhance the investor confidence at large. There are a number of studies which argue, corporate governance and its mechanisms or proxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 17 publications
0
1
1
Order By: Relevance
“…Nevertheless, the outcomes did not conform to the findings of some past empirical works (Abu Qa'dan & Suwaidan, 2019;Cucari, Esposito De Falco, & Orlando, 2018;Khan, Khan, & Saeed, 2019;Muntaha & Haryono, 2021;Sahore & Verma, 2019).…”
Section: Discussion Of Findingscontrasting
confidence: 83%
See 1 more Smart Citation
“…Nevertheless, the outcomes did not conform to the findings of some past empirical works (Abu Qa'dan & Suwaidan, 2019;Cucari, Esposito De Falco, & Orlando, 2018;Khan, Khan, & Saeed, 2019;Muntaha & Haryono, 2021;Sahore & Verma, 2019).…”
Section: Discussion Of Findingscontrasting
confidence: 83%
“…The study of Khan, Khan, and Saeed (2019) showed that educational qualification of directors is negatively associated with company social practices disclosure. Likewise, the study of Sahore and Verma (2019) revealed that the relationship between board independent directors and voluntary disclosure is not significant. As well, Qoyum, Mutmainah, Setyono, and Qizam (2017) found that board of commissioners' independent is negatively related to company social responsibility reporting in Islamic banking.…”
Section: Review Of Extant Literaturementioning
confidence: 96%